2005
DOI: 10.1007/s00436-005-1459-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel genotype of Cryptosporidium muris from large Japanese field mice, Apodemus speciosus

Abstract: Cryptosporidium muris-like oocysts were isolated from large Japanese field mice, Apodemus speciosus. Morphologically, these oocysts resembled those obtained from a C. andersoni Kawatabi isolate but were smaller in size than those from a C.muris isolate. Following oral inoculation of the oocysts into large Japanese field mice and SCID mice, developing stages were found in the stomach epithelium. The infectivity of the isolate to wild and laboratory mice was slightly different from that of C.muris. DNA sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 29 publications
0
23
0
1
Order By: Relevance
“…A parasite identical to the C. muris East African mole rat isolate was previously identified in an eastern gray squirrel in New York (6), suggesting that this parasite is probably widespread. A C. muris isolate from Japanese field mice was also shown to have minor differences in mouse infectivity and the sequence of the SSU rRNA gene from other C. muris isolates (16). Thus, genetic and biological diversities exist in C. muris, and with the inclusion of more genetic loci and samples from a wide range of hosts and geographical areas, the MLST approach developed in this study should be useful in elucidating the genetic basis for the difference in host specificity among C. muris isolates and in examining the spread of the parasite in geographically isolated areas such as the continent of Australia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A parasite identical to the C. muris East African mole rat isolate was previously identified in an eastern gray squirrel in New York (6), suggesting that this parasite is probably widespread. A C. muris isolate from Japanese field mice was also shown to have minor differences in mouse infectivity and the sequence of the SSU rRNA gene from other C. muris isolates (16). Thus, genetic and biological diversities exist in C. muris, and with the inclusion of more genetic loci and samples from a wide range of hosts and geographical areas, the MLST approach developed in this study should be useful in elucidating the genetic basis for the difference in host specificity among C. muris isolates and in examining the spread of the parasite in geographically isolated areas such as the continent of Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic relationships among subtypes of C. muris, the C. muris variant, and C. andersoni as assessed by a neighbor-joining analysis of the concatenated nucleotide sequences of four microsatellite and minisatellite loci (MS1, MS2, MS3, and MS16), using distance calculated by the Kimura two-parameter model. 3 and (GAACGA GATAGG) [14][15][16][17][18] (TAAAGAGAGAGA) 6 and (GAACGAGATAGG) 14 (TAAAGGGCGAGA) 3 and (GAACGAGATAGG) 13-14 CM-MS2 (CCATATCCC) [3][4] and (CCATACCTC) 3 (CCCATTCCT) 4 (CCATACCTC) 10-11 CM-MS3 (TGTTGG) [8][9] and (GCTGCA) 6 (TGTTGG) 7 and (TGC) 10 (TGTTGGTGTTGCTGT) 2 and (TGCTGCAGCTGC) 2-3 CM-MS16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been few studies conducted on the epidemiology of Cryptosporidium in wild mice; however, it is important to understand if mice are a reservoir of infection for humans and animals. Studies in different geographical areas have reported prevalence rates ranging from 5.0% to 39.2% in wild rodents, but most have relied on morphology for identification (2)(3)(4)(20)(21)(22).The limited molecular characterization studies that have been conducted on rodents have identified eight species/genotypes: (i) mouse genotype I, which has been identified in mice and rats and in prairie bison in Spain, Portugal, the United Kingdom, Australia, and the United States (1, 16; L. Xiao et al, unpublished data) and to date has not been identified in humans; (ii) the zoonotic Cryptosporidium parvum, which was detected in mice trapped near sheep grazing pastures in Victoria, Australia (16); (iii) Cryptosporidium muris, which infects a range of rodents and is generally not zoonotic but which can infect other hosts, including dogs, hamsters, guinea pigs, chipmunks, rabbits, lambs, cats, and humans (4,9,10,11,18,19); (iv) a novel genotype detected in one wood mouse (Apodemus sylvaticus) sample from the Czech Republic (8); (v) Cryptosporidium meleagridis, isolated from a brown rat (Rattus norvegicus) in Japan (isolate BR5) (13); (vi) eight isolates from brown rats in Japan that clustered with sequences denoted W19 and W19 variants found in New York storm water (12, 13); (vii) three isolates from brown rats in Japan identical to recently described snake isolate 2162 (AY268584) (13, 25); and (viii) another isolate from brown rats in Japan which showed 100% identity with isolates from nonhuman primates in Sri Lanka (EF446679) (5, 13).These studies indicate that the majority of wild mice characterized to date do not carry zoonotic species of Cryptosporidium. …”
mentioning
confidence: 99%
“…As reference strains, we used oocysts of C. parvum HNJ-1 (Masuda et al 1991), C. muris RN66 (Iseki 1986), C. andersoni Kawatabi strain (Satoh et al 2003), and C. muris Japanese field mouse genotype (Hikosaka and Nakai 2005). These oocysts had been passaged and maintained in the severe combined immunodeficiency (SCID) mice in our laboratory, and the oocysts were purified from the fecal sample of the experimental infected SCID mice using sugar floatation method (Nakai et al 2004).…”
Section: Methodsmentioning
confidence: 99%